Early Loading after Closed Wedge High Tibial Osteotomy for Knee Arthritis - Golovakha, M. L.; Aghayev, Emin; Orljanski, Wenjamin (My University, 2015)
Operative treatment approaches for the arthritis in the medial tibiofemoral compartment combined with a varus deformation of the knee are closed wedge high tibial osteotomy or knee arthroplasty. In contrast to the knee arthroplasty, tibial osteotomy maintains primary the function of natural knee joint. However, the limitations of the method are the necessity of postoperative immobilization, late term of loading and long period of functional recovery. The study on early loading after closed wedge high tibial osteotomy as the treatment of knee arthrosis was initiated. Two group of different postoperative rehabilitation approach were allocated. The first group included 22 patients in whom the loading was applied after 6th postoperative week, and the second group included 15 patients with early weight bearing at 3rd-5th postoperative day. Estimation of complications and comparison of the results of the treatment in two groups was carried out. The short- and long-term results of the treatment in the both groups showed similar distribution of good and poor result without significant differences. Studying rehabilitation dynamic, early loading allowed for faster postoperative functional recovery. No statistically significant differences regarding postoperative complications between the groups were observed. Our results indicate that early weight bearing after high tibial osteotomy does not worsen process of rehabilitation and result of the treatment. The absence of statistical differences regarding postoperative complications indicates the safety of the approach. In conclusion, we assumed that after closed wedge high tibial osteotomy the early postoperative loading is an advantageous rehabilitation approach in comparison with the late loading due to a faster functional recovery and a shortening of the patient hospitalisation. Nevertheless, further multipatient studies on this approach with similar long-term follow ups are necessary
Keywords: Knee; Arthritis; High tibial osteotomy; Loading; Closed wedge